2019
DOI: 10.2478/picbe-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Investors’ rationality. An analysis of the investment policy implications on shares valuation

Abstract: The investment policy is an important vehicle of growth for a company. Therefore, it should be one of the most important signals for investors on the capital market. We use the statistical analysis of the investors’ reactions to different patterns of investment policy to highlight their preference for an active investment policy and the changes induced by the financial crisis. By a comparative analysis of investors’ preferences with the information on the accounting-based performance recorded simultaneously an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…We reported only the percentage from the comparison with the average levels because the ones from the comparison with the median are similar. We observed that the differences between the two classes of countries for category A were relatively small and that their evolution was similar to the one determined for the global market put in evidence in [27], thus providing the same conclusion: The markets were signaling a preference for higher levels of investment. This suggests that the country level of economic development did not have a major influence on the results of our analysis.…”
Section: The Market Preference For Investmentssupporting
confidence: 77%
See 4 more Smart Citations
“…We reported only the percentage from the comparison with the average levels because the ones from the comparison with the median are similar. We observed that the differences between the two classes of countries for category A were relatively small and that their evolution was similar to the one determined for the global market put in evidence in [27], thus providing the same conclusion: The markets were signaling a preference for higher levels of investment. This suggests that the country level of economic development did not have a major influence on the results of our analysis.…”
Section: The Market Preference For Investmentssupporting
confidence: 77%
“…The results we obtained are presented in Table 7. The levels for category A are similar to the ones for the global market [27], indicating a signal for similar preferences. However, there was a difference in the evolution of these levels.…”
Section: The Market Preference For Investmentsmentioning
confidence: 56%
See 3 more Smart Citations